THE RELATIONSHIP BETWEEN JEAN WATSON'S THEORY OF HELPING TRUST WITH PATIENT SATISFACTION - Shieva Nur Azizah Ahmad; Cicih Ayu Yulianti; Roswita Hasan (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Fostering a trusting relationship between nurses and patients is the development of one of the curative caring factors because it is closely related to the acceptance of positive and negative feelings of patients when receiving services from nurses. The quality of a person's relationship with others is an element that determines the caring behavior of a nurse (Sartika, 2011). Nurses must be patient, generous, willing to provide assistance to patients voluntarily and be able to communicate, work and be responsible for their duties and rights when acting (Nursalam, 2013).Objectives: The purpose of this study was to determine Jean Watson's theory of helping trust with patient satisfaction in the inpatient room in The Government Hospital of Tangerang Regency.Methods: The research design used in this study is descriptive correlation using the Cross-Sectional approach. The population used in this study were patients treated in the inpatient rooms of Government Hospital of Tangerang Regency amounting to 80 people. The sampling method used is the non-probability sampling method. The sampling technique in this research is purposive sampling. The sample used in this study were 65 respondents. This research instrument using a questionnaire. The analysis used the Chi square test with a significance level α < 0.05.Results: Jean Watson's helping trust relationship both 13 respondents (34.2%) and those who were not satisfied were 1 respondent (3.7%). the results of the analysis obtained OR = 25.35 means that patients who claim helping trust relationship Jean Watson have a 25.35 times chance expressed satisfied. Chi square test results obtained p value 0.001 so that it can be concluded that there is a significant relationship between Jean Watson’s theory of helping trust relationship with patient satisfaction in class III inpatient room at The Government Hospital of Tangerang Regency.Conclusion: Patient satisfaction depends on the quality of nursing services. Service is said to be good if in fact the nurse provides the needs according to the patient's condition and the patient's response to service can be disappointing or satisfying. Further research is expected that nurses can provide assistance to the relationship of trust to patients so that patients can feel safe and comfortable when nurses take nursing actions to patients. Further researchers can use other research methods either qualitatively or add other variables so that the helping trust relationship between nurses and patients can be well developed. Keywords: Helping Trust Relationship, Patient, Satisfaction, Jean Watson.